2018
DOI: 10.1002/cphc.201801055
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Direct Evidence of the Benzylium and Tropylium Cations as the Two Long‐Lived Isomers of C7H7+ (ChemPhysChem 23/2018)

Abstract: The Cover Feature shows C7H7+ produced by dissociative ionization of toluene. Combining cryogenic trapping with infrared pre‐dissociation spectroscopy, two structures could be identified: the benzylium and tropylium ions. More information can be found in the Communication by P. Jusko et al. on page 3182 in Issue 23, 2018 (DOI: 10.1002/cphc.201800744).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…population of the phen 2+ isomer and consequently a change in the peak intensity of phen 2+ bands relative to the anth 2+ bands. This method was successfully implemented for benzylium and tropylium cations (C 7 H 7 + ), two isomers formed in dissociative ionization of toluene (Jusko et al 2018a), but we did not observe any change in the peak intensity for any of the phen 2+ bands. Instead, the intensity of the phen 2+ bands decreased over time during the measurement campaign, leading us to conclude that they are due to contamination instead of isomerization.…”
Section: Anthracenementioning
confidence: 72%
See 2 more Smart Citations
“…population of the phen 2+ isomer and consequently a change in the peak intensity of phen 2+ bands relative to the anth 2+ bands. This method was successfully implemented for benzylium and tropylium cations (C 7 H 7 + ), two isomers formed in dissociative ionization of toluene (Jusko et al 2018a), but we did not observe any change in the peak intensity for any of the phen 2+ bands. Instead, the intensity of the phen 2+ bands decreased over time during the measurement campaign, leading us to conclude that they are due to contamination instead of isomerization.…”
Section: Anthracenementioning
confidence: 72%
“…To account for fluctuations in the number of complex ions and varying laser energy during the course of a single scan, the spectra were normalized to laser pulse energy and baseline corrected before averaging over multiple scans. Saturation depletion measurements allowed us to decode the isomer ratios of molecular ions having two or more stable structures, see, for example, Jusko et al (2018a). A detailed account of this technique is discussed in Jusko et al (2019).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for fluctuations in the number of complex ions and varying laser energy during the course of a single scan, the spectra were normalized to laser pulse energy and baseline corrected before averaging over multiple scans. Saturation depletion measurements allowed us to decode the isomer ratios of molecular ions having two or more stable structures, see, for example, Jusko et al (2018a). A detailed account of this technique is discussed in Jusko et al (2019).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In the past, these techniques have been successfully employed to elucidate the isomeric composition of cationic fragmentation products upon dissociative ionization of PAHs and related species. Using IRPD in a cryogenic ion trap, Jusko et al 23 recorded the mid-IR spectra of Ne-tagged C 7 H 7 + and revealed its two isomeric forms, i.e., benzylium + and tropylium + . Ne-tagged doubly dehydrogenated pyrene (ddPy + ) was spectroscopically investigated using the same technique by Panchagnula et al 24 The results showed that its spectral features correspond to a mixture of different isomers (4,5-ddPy + and 1,2-ddPy + ) favoured by the loss of hydrogen from the same aromatic ring.…”
Section: Introductionmentioning
confidence: 99%